Model Pengembangan Dakwah Berbasis Budaya Lokal - Moch. Anif Arifani (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
Da’wah and local culture have tight relations. Each da’wah events always exist in interacts with its around. How is da’wah subject doing activity and how is da’wah object (mad’u) behaving in da’wah event of course always bring and involve its culture background. Da’wah approach not only use culture as da’wah medium but also in knowing mad’u strata. The religious leaders as da’wah agent in java have done spreading by culture approach such using culture medium, art, lyrics, unique fashion, and so on.